GAMBARAN POLA MAKAN, AKTIVITAS FISIK, DAN STATUS GIZI SISWA SEKOLAH DASAR LUAR BIASA (SDLB) NEGERI 057704 KWALA BINGAI KECAMATAN STABAT TAHUN 2016 - Margaretha Pasaribu; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Primary student experiencing relatively rapid growth, and require nutrients in relatively large amounts. However, 80% of children with developmental disorders have trouble eating. Physical activity of children with intellectual disabilities is lower compared to normal children. There are differences in the nutritional status of children with disabilities with normal children. This study aimed to describe diet, physical activity and nutritional status of students 057704 SDLBN Kwala Bingai District of Stabat 2016. Type of research was observational with cross sectional design. This study was conducted to assess the food composition, calculate energy and protein consumption using 24-hour food recall and food frequency. Calculating physical activity and nutritional status of BMI/A and H/A students. The research sample were 62 people who are retarded and deaf students. The sampling technique was purposive sampling. Student’s body weight was measured by weights and body height was measured by microtoise. Data Analysis used descriptive analysis. The result of study showed in general,studentfood composition was 58,1% incomplete, .food energy consumption  61,3% relatively less, and 53,2% protein consumption quite well. Most students frequently eat fish and eggs as side dishes, cassava leaves and spinach as a vegetable,bananas and oranges as fruit. Students' physical activity 79,0% classified as mild. Students with BMI/A obese haveH/A short by 33,3% and 22,2% very short. Cooperate of the health service is health center with the school in order to provide nutrition education about feeding the child to the mother’s student. And to improve the monitoring of the nutritional status of students. Mother of students pay more attention to children’s food consumption and involve children in sports activities at school. Keywords: Diet,physical activity,nutritionalstatus,extraordinary primary srudent